How Does the Rohingya Influx Influence the Residential Satisfaction and Mobility Intentions of the Host Communities in Bangladesh? - Bangkim Biswas; Bishawjit Mallick; Nasif Ahsan; Rupkatha Priodarshini (Journal of International Migration and Integration, 2021)
This study investigates the residential satisfaction and future relocation intention of the host communities neighbouring Rohingya migrants in Bangladesh. An empirical study of 151 households was conducted in Ukhiya and Ramu Upazila of Cox's Bazar district in late 2019. The residential satisfaction component includes the social environment (SE), neighbourhood environment (NE), and public services and facilities (PS&F). It shows that, due to the Rohingya influx, the residential satisfaction level of the Ukhiya host communities declined by 30.17%. Besides, to determine factors that impact on the intention to migrate, the ordinal logistic regression model has been run. A larger distance between the household and the Rohingya camps, longer duration of residence in the community, and a higher number of children in the family negatively influence the mobility intention of the host communities. Furthermore, the Hindu residents in the host communities have higher propensity to relocate. These findings demand that policies and programmes should be planned in a way that enables the host communities to stay in place despite the Rohingya influx.
Keywords: 300; Residential satisfaction; Intention to relocation; Influx of Rohingya; Host communities; Bangladesh